ANALYSIS OF THE COMPETITIVENESS OF INDONESIAN COFFEE EXPORTS TO MAJOR DESTINATION COUNTRIES - Gadis Dyah Pavita; Suandi Suandi; Ardhiyan Saputra; Mirawati Yanita (Universitas Sebelas Maret, 2026)
Coffee is a leading Indonesian plantation commodity vital to international trade. However, export performance to major destinations fluctuates due to global market dynamics and rising competition. This study aims to describe Indonesian coffee export volume trends to major destination countries and to analyze their competitiveness. The analyzed markets include the United States, Malaysia, Egypt, India, Italy, and Japan. The study employs Revealed Comparative Advantage (RCA), Export Competitiveness Index (ECI), Trade Specialization Index (TSI), and Constant Market Share (CMS) using secondary data (1991–2024) under HS Code 0901 from the UN Comtrade database. Results indicate that export volumes fluctuate with varying trends across markets. RCA findings show that Indonesian coffee generally maintains a comparative advantage in most destinations. However, ECI results reveal weak competitive performance in Italy and Japan, reflecting declining competitiveness. Furthermore, CMS analysis shows that Indonesian coffee exhibits competitive performance only in the Egyptian market. Conversely, export growth in the United States, Malaysia, Italy, Japan, and India remains below global trade growth, characterized by weak competitive effects. These findings suggest the necessity of market-specific strategies to strengthen Indonesia’s coffee export competitiveness globally.